P10.02 Differentiating microglia and tumour associated macrophages in high grade glioma. (6th September 2019) - Woolf, Z; Swanson, M; Park, T; Brooks, A; Dragunow, M
Abstract: BACKGROUND: Glioblastoma multiforme (GBM) is the most common primary brain tumour that affects adults. This aggressive tumour is invariably fatal, carrying a rapid progression and a dismal median survival period of only 15 months despite multimodal treatment approaches. Central to GBM pathogenesis is the immunosuppressive profile of these tumours. The two cell types that are highly abundant in these tumours and play critical roles in the immunosuppressive niche are the brain's resident microglia and their peripheral counterparts - tumour associated macrophages (TAMs). Despite microglia and TAMs being ontogenetically distinct, these cells have largely been grouped together in research owing to the previous lack of cell-specific markers. Recent evidence has suggested that although TAMs may hold a predominantly pro-tumoral role, microglia may adopt a more anti-tumoral phenotype. Therefore, the differentiation of these two cell types is critical in elucidating the potentially characteristic roles of these two cell types in GBM pathogenesis. MATERIAL AND METHODS: Tissue sections from resected low- and high-grade glioma tumours, along with epilepsy tissue (control), were used for immunohistochemistry (IHC) staining of macrophage pan-makers (Iba1, CD45, PU.1) and microglial-specific markers (TMEM119, P2RY12). Marker co-localisation was then used to differentiate microglia from TAMs. We further investigated a wider subset of cell-specific markers using multicolour flow cytometry and immunocytochemical staining of isolated cells from patient tissue samples. RESULTS: Immunofluorescent staining of glioma and epilepsy tissue revealed two clear populations of cells; one population displayed long processes and co-labelling for both pan- and microglial-specific markers, whilst the other population displayed an amoeboid phenotype with only pan-maker staining. Preliminary analysis comparing microglia/TAM populations in low-grade, high-grade and epilepsy tissue suggests a clear difference in the proportions of these cells. CONCLUSION: Our work complements RNA-Seq studies, showing that TMEM119 and P2RY12, alongside other markers, can indeed identify two distinct myeloid cell populations within glioma tissue. This provides a strong basis for further study where we aim to elucidate the respective roles of microglia and TAMs within tumours. Ultimately, this may hold the potential for differential targeting of these cells using immunotherapies.